Analysis of Superior Commodities in Agricultural Sector in Some Districts of North Sumatera Province - Lubis, Nela Permata Sari; Nugrahadi, Eko Wahyu; Yusuf, M. (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Realization of regional economic development requires policies that are endogenous development. Each region has a base sector as the main driving force in economic growth. The base sector must have resilience between other sectors and have a high contribution to the formation of total regional economic output. North Sumatra is one of the provinces in Indonesia which has a tendency towards economic structure in the agricultural sector. Viewed from the field of business, the agricultural sector provides the highest contribution in the formation of GRDP. North Sumatra has 25 districts with a variety of geographical conditions having varied natural resources that need to be intensified and explored. The purpose of this study is to analyze the leading commodities of the agricultural sector and find out how much the impact of the leading sector on the growth of North Sumatra GRDP in the period 2014 - 2018. The method of analysis in this study uses the Location Quotient (LQ) analysis, Revelead Comparative Advantage (RCA) analysis, and Panel Data Regression Analysis. The estimation results show that the agriculture, livestock, hunting and services sub-sectors, the forestry sub-sector and the fisheries sub-sector have a positive and significant effect on the economic growth of the province of North Sumatra. The economic growth variables can be explained by 89 percent by the variables of the agriculture, livestock, hunting and service subsectors, the forestry subsector and the fisheries subsector while the rest are explained by variables not included in this study.